Maintenance vs. Change of Negative Therapy Expectation: An Experimental Investigation Using Video Samples - Braun-Koch, Kristina; Rief, Winfried (Frontiers in Psychiatry, 2022)
Introduction: Therapy expectations contribute substantially to the outcome of psychotherapy. In contrast, psychotherapy expectations are rarely addressed and systematically optimized in studies on psychotherapy. Materials & Methods: A total of 142 subjects with critical attitudes towards psychotherapy were randomized into two groups: (1) a control group that watched a video with patients who gave information about their symptoms or (2) an experimental group that watched an expectation-optimized video with the same patients giving additional information about their mostly positive therapy outcomes. The primary outcome was the Milwaukee Psychotherapy Expectation Questionnaire (MPEQ), which was filled in before and after watching the video. Results: Both groups showed a significant improvement of their expectations and attitudes towards psychotherapy after watching the video. Subjects in the experimental group changed their therapy outcome expectation more substantially (F (1,140) = 9.72, p = .002, η2 = .065). Conclusions: A video intervention with patients presenting their positive therapy experiences improves therapy expectations in persons with critical attitudes. Expectation-optimized videos could be used for prevention programmes and when starting therapy.